Measurements of tropospheric HO2 and RO2 by oxygen dilution modulation and chemical ionization mass spectrometry - J. S. Olson (Atmospheric Measurement Techniques, 2011)
An improved method for the measurement of hydroperoxy radicals (HO2) and organic peroxy radicals (RO2, where R is any organic group) has been developed that combines two previous chemical conversion/chemical ionization mass spectrometry (CIMS) peroxy radical measurement techniques. Applicable to both ground-based and aircraft platforms, the method provides good separation between HO2 and RO2, and frequent measurement capability with observations of both HO2 and HO2 + RO2 amounts each minute. These improvements allow for analyses of measured [HO2]/[HO2 + RO2] ratios on timescales relevant to tropospheric photochemistry. By varying both [NO] and [O2] simultaneously in the chemical conversion region of the PeRCIMS (Peroxy Radical CIMS) inlet, the method exploits the changing conversion efficiency of RO2 to HO2 under different inlet [NO]/[O2] to selectively observe either primarily HO2 or the sum of HO2 and RO2. Two modes of operation have been established for ambient measurements: in the first half of the minute, RO2 radicals are measured at close to 100% efficiency along with HO2 radicals (low [NO]/[O2] = 2.53 × 10−5) and in the second half of the minute, HO2 is detected while the majority of ambient RO2 radicals are measured with low efficiency, approximately 15% (high [NO]/[O2] = 6.80 × 10−4). The method has been tested extensively in the laboratory under various conditions and for a variety of organic peroxy radicals relevant to the atmosphere and the results of these tests are presented. The modified PeRCIMS instrument has been deployed successfully using the new measurement technique on a number of aircraft campaigns, including on the NSF/NCAR C-130 during the MIRAGE-Mex and NASA INTEX-B field campaigns in the spring of 2006. A brief comparison of the peroxy radical measurements during these campaigns to a photochemical box model indicates good agreement under tropospheric conditions where NOx (NO + NO2) concentrations are lower than 0.5 ppbV (parts per billion by volume).